-2 * (-3)^2
First simplify the exponents:
-2 * 9
Now multiply for final answer:
-18
Center of the circle: C=(3,8)=(h,k)→h=3, k=8
Radius of the circle: r=5
Standard form of the equation for the circle:
(x-h)^2+(y-k)^2=r^2
(x-3)^2+(y-8)^2=5^2
(x-3)^2+(y-8)^2=25
General for of the equation for the circle:
(x)^2-2(x)(3)+(3)^2+(y)^2-2(y)(8)+(8)^2=25
x^2-6x+9+y^2-16y+64=25
x^2+y^2-6x-16y+73=25
x^2+y^2-6x-16y+73-25=25-25
x^2+y^2-6x-16y+48=0
Answer: The general form of the equation for the circle is:
x^2+y^2-6x-16y+48=0
Answer: ![-4\left(\frac{1}{2} \right)^{x}](https://tex.z-dn.net/?f=-4%5Cleft%28%5Cfrac%7B1%7D%7B2%7D%20%5Cright%29%5E%7Bx%7D)
Step-by-step explanation:
To reflect the graph of a function across the x-axis,
![y=f(x) \longrightarrow y=-f(x)](https://tex.z-dn.net/?f=y%3Df%28x%29%20%5Clongrightarrow%20y%3D-f%28x%29)
Answer : a judgement error
explanation:
I don’t know because I think you copied the question wrong